Penerapan Sanksi Administratif Terhadap Notaris Yang Melakukan Pelanggaran Terhadap Jabatannya (Studi Putusan Pengadilan Tata Usaha Negara No. 235/G/2019/PTUN.KT) - Marcelina Siti Nabila; Pieter E. Latumeten (UNES Law Review, 2023)
Notaries as public officials in carrying out their positions must comply with the Law on Notary Positions and the Notary Code of Ethics. The implementation of administrative sanctions against notaries who have violated their position is the authority of the Notary Supervisory Council and the Minister of Law and Human Rights. MPN in imposing sanctions on notaries cannot act arbitrarily. In the Decision of the State Administrative Court No. 235/G/2019/PTUN.KT, the MPN imposes sanctions for dishonorably dismissing a notary for violations in the form of signing a deed outside the Notary's office area, not providing a copy of the deed to the parties, and in carrying out his or her position not acting in a trustworthy, honest, thorough and effective manner. independent. In this case, the author examines whether the administration of administrative sanctions carried out by MPN is in accordance with the Law on Notary Positions and the Regulation of the Minister of Law and Human Rights concerning Procedures for Imposing Administrative Sanctions. This research is normative legal research which is known as research for academic purposes. namely the process of searching for legal rules, legal doctrines, and legal principles to answer the legal issues being discussed.